Formulation and optimization of liquisolid compact for enhancing dissolution properties of efavirenz by using DoE approach - Bhola Jaydip; Mori Dhaval; M.M. Soniwala; Jayant Chavda (Saudi Pharmaceutical Journal, 2020)
Efavirenz displays low and variable bioavailability because of its poor aqueous solubility and high log P-value. The present investigation was aimed to improve the dissolution profile of efavirenz by using a simple, scalable and cost-effective technique of liquisolid compact. The drug was dissolved in Trancutol-HP for preparing the liquid medicament which was subsequently mixed with carrier and coating material to make free-flowing and compressible powder. 32 full factorial design was used to optimize the formulation in which the Neusilin US2/Corn starch ratios and carrier/coating material ratio were selected as independent variables. The results of in-vitro dissolution test proved that liquisolid compacts have significantly higher dissolution rate than tablets containing pure drug. Results of DSC and XRD studies suggested that the high dissolution of the drug from the liquisolid compacts was possibly because of the drug either being in an amorphous state or being molecularly dispersed within the internal matrix of compacts.